ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RETURN SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Ina,; Agus Defri Yando, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Return in the investment world means the return of the proceeds in the form of profit or earns on previous decisions which have made by investor. In this paper, testing is carried out to determine how the influence of operating cash flow, accounting profit and company size on stock returns in the banking sub-sector companies listed on the Indonesia Stock Exchange. Technique that used on research is purposive sampling technique, with the results there are 10 companies selected from the population. By using the analysis method of the research model which is multiple linear regression analysis. Data of study which used by researcher is financial data from the Indonesia Stock Exchange Riau Islands Representative Office. This research is using SPSS version 25 application program in conducting the testing. The results showed that stock returns are influenced by the size of the company. However, stock returns are not affected by operating cash flows and accounting earnings while simultaneously showing no effect of operating cash flows, accounting earnings and size on stock returns.